KONSEP DIR ANGGOTA MAHASISWA PECINTA ALAM FISIP UNIVERSITAS RIAU - Putra, Riswanto Adi; Sari, Genny Gustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Student neture lover, for the member is only as a community, but it has been became a life for the member. Is their opinions, student neture lover is the second home. Almost everty night, thet gather is the homestay to do activities, such as singing, culding, it is like the campus is never silent. They are look like a mess and careless with their performance, that convince their characteristic as the member of student neture love. This study aims to knowing the underlying motive behind self, concept of member and self aspects are formed on student neture lover.This study is using phenomenology approaching and data collection is using purposive sampling ammount to five, with data collections technique is in depth interview participant, oberservation participant, and documentation. Meanwhile, for validity correction terchinique, the resercher is using extension opt-in techinique and the then the reseracher is processing the data for reducted and presented until produce generai conlusion.The result of this study indicate that the underlying motive behind the student become student neture lover because there is hobby, enveronmental of domicile and nateru activities. The factors that affect self-concept of student nature lover, because there is education factor, teach the each member to become discipline persone, form the characteristic, caring the neture, the other can giving information about student neture lover that thery get form student camp, member and senior Fisip (Faculty of Social and Political Science) and aapects of self, concept are formed on student neture lover, they are psychic, comfortable as a member, and social aspects because there is caring for the others affeected by disaster.Keywords: Concept self, Student Neture Lover